EVALUASI PROGRAM KESEJAHTERAAN SOSIAL ANAK TERLANTAR (PKSAT) DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) MADANI BANTEN - Siti Nurul Hamidah; Uzieka Arsiya Rosadha; Ari Alfiansyah; Abdul Hafidz Sufiyana; Mutamimatussifah Mutamimatussifah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
The Social Welfare Program for Displaced Children (PKSAT) is a program created to address the problems of displaced children. One of the institutions that implement the PKSAT program is the Children's Social Welfare Institute (LKSA) Madani Banten through religious programs. The purpose of this research is to determine the evaluation of PKSAT program using CIPP evaluation model (Context, Input, Process, Product). The research method used is a descriptive qualitative approach. Cipp program evaluation includes (1) context evaluation consisting of background, objectives and needs analysis, (2) input evaluation, consisting of 4 aspects, namely implementing, budget allocation, targets, facilities and infrastructure, (3) Evaluation Process, which is divided into 4 parts, namely: Planning and socialization, implementation, monitoring and evaluation of programs, (4) Product Evaluation, which consists of program results. The results of the evaluation research showed that the program implemented in LKSA Madani can be achieved well despite constraints in the program budget.